One-Year Clinical Outcome after Left Ventricular Assist Device Malfunction - Oezpeker, U. Cenk; Zittermann, Armin; Erkilet, Guelsuem; Schulz, Uwe; Ensminger, Stephan; Gummert, Jan F.; Morshuis, Michiel (The Thoracic and Cardiovascular Surgeon, 2015)
Background Left ventricular assist device (LVAD) implants bear the risk of driveline/device infections and technical failures.Methods We assessed clinical outcome in LVAD patients with device-related complications. Group 1 (n = 12) received device exchange (DEx) as destination therapy (DT), group 2 (n = 15) received DEx as a bridge to transplant (BTT), group 3 (n = 34) was allocated to receive high-urgency (HU) heart transplantation (HTx), and group 4 (n = 27) had device-related complications that could only be solved by HTx. Primary endpoint was 1-year overall survival.Results Age and Simplified Acute Physiology Score II differed significantly between groups and were highest in group 1, lowest in group 3. One-year survival in groups 1 to 4 was 66.7, 60.0, 82.4, and 70.4% (p = 0.30). Covariate-adjusted odds ratio of 1-year survival (reference: group 1) was for group 2 = 1.52 (95% confidence interval [CI]: 0.42–5.57), for group 3 = 1.13 (95% CI: 0.28–4.56), and for group 4 = 1.89 (95% CI: 0.51–7.04; p for trend 0.70). Clinical complications (need of mechanical ventilator support, extracorporeal circulatory membrane oxygenation (ECMO) implants, kidney/liver dialysis) were comparable between groups.Conclusion Data indicate similar 1-year clinical outcomes in LVAD patients with device-related complications receiving DEx or HTx.
Keywords: left ventricular assist device; device malfunction; device exchange; heart transplantation; destination therapy; bridge to transplant